Multiple Rice MicroRNAs Are Involved in Immunity against the Blast Fungus Magnaporthe oryzae . Issue 2 (13th December 2013) - Li, Yan; Lu, Yuan-Gen; Shi, Yi; Wu, Liang; Xu, Yong-Ju; Huang, Fu; Guo, Xiao-Yi; Zhang, Yong; Fan, Jing; Zhao, Ji-Qun; Zhang, Hong-Yu; Xu, Pei-Zhou; et al.
Abstract : Multiple microRNAs differentially responsive to the infection of the blast fungus Magnaporthe oryzae and identify two that elevated resistance to the disease . Abstract: MicroRNAs (miRNA s) are indispensable regulators for development and defense in eukaryotes. However, the miRNA species have not been explored for rice ( Oryza sativa ) immunity against the blast fungus Magnaporthe oryzae, the most devastating fungal pathogen in rice production worldwide. Here, by deep sequencing small RNA libraries from susceptible and resistant lines in normal conditions and upon M. oryzae infection, we identified a group of known rice miRNA s that were differentially expressed upon M. oryzae infection. They were further classified into three classes based on their expression patterns in the susceptible japonica line Lijiangxin Tuan Hegu and in the resistant line International Rice Blast Line Pyricularia-Kanto51-m-Tsuyuake that contains a single resistance gene locus, Pyricularia-Kanto 51-m (Pikm), within the Lijiangxin Tuan Hegu background. RNA-blot assay of nine of them confirmed sequencing results. Real-time reverse transcription-polymerase chain reaction assay showed that the expression of some target genes was negatively correlated with the expression of miRNA s. Moreover, transgenic rice plants overexpressing miR160a and miR398b displayed enhanced resistance to M. oryzae, as demonstrated by decreased fungal growth, increased hydrogen peroxide accumulation at the infection site, and up-regulated expression of defense-related genes. Taken together, our data indicate that miRNA s are involved in rice immunity against M. oryzae and that overexpression of miR160a or miR398b can enhance rice resistance to the disease.